Impact of a Developmental Care Training Course on the Knowledge and Satisfaction of Health Care Professionals in Neonatal Units: A Multicenter Study - Rocío Mosqueda-Peña; David Lora-Pablos; Abraham Pavón-Muñoz; Noelia Ureta-Velasco; María Teresa Moral-Pumarega; Carmen Rosa Pallás-Alonso (Pediatrics and Neonatology)
The impact of health-related continuing education courses on knowledge acquisition and clinical practice is infrequently evaluated, despite higher numbers of people enrolling in them. The majority of health care professionals working in neonatal intensive care units (NICUs) have received no training in developmental care (DC). The purpose of this study was to determine whether participation in a theoretical-practical course on DC had an effect on the degree of knowledge possessed by professionals in general terms and with respect to neonatal intensive care. The relationship between course satisfaction and knowledge acquisition was also studied. Methods: This was an observational multicenter study conducted in 20 neonatal units in Madrid. A pre- and post-course questionnaire evaluated both knowledge and satisfaction levels regarding the course on DC and the Newborn Individualized Developmental Care and Assessment Program (NIDCAP). We carried out a multivariate linear regression analysis to determine whether there was a correlation between knowledge gained and satisfaction level. Results: A total of 566 professionals participated, with a 99% pre-course and a 90% post-course response rate. The mean rate of correct pre-course answers was 65%, while the mean rate of post-course correct answers was 81% (p < 0.001). Results were similar at all levels of neonatal care (Level I: 64% vs 80%; Level II: 64% vs. 83%; and Level III: 65% vs. 81%). Scores on a scale of satisfaction from 1 to 5 were high (averages of above 4 for all lectures and workshops). Pre-course knowledge scores, but not satisfaction, significantly influenced post-course knowledge (β 0.499; p < 0.01). Conclusion: Previous DC knowledge among Madrid health care professionals was similar, regardless of the level of neonatal care. Course attendance significantly improved the rate of correct answers. Although course satisfaction was high, there did not seem to be a correlation between knowledge gained and satisfaction.